Computer agents that help students leran with intelligent strategies and emotional sensitivity - Graeser, Arthur C.; D'Mello, Sidney K.; Strain, Amber C.
Computer agents have been designed to help students learn subject matters by holding conversations with the students in natural language. For example, AutoTutor improves learning of subject matters such as computer literacy and conceptual physics by co-constructing explanations and answers to complex questions (why, how, what if, etc.). One version of AutoTutor is sensitive to the affective states of the learners in addition to their cognitive states and also responds with emotions designed to facilitate learning. These computer agents simulate the cognitive and metacognitive strategies of novice human tutors in addition to incorporating ideal pedagogical strategies of expert tutors. The agents are not perfect conversation partners and comprehenders of language, but the conversations are surprisingly coherent and also help students learn.
Keywords: Agents; Tutoring; Discourse; Learning technologies; Emotions